Do professional investors behave differently than amateurs after the weekend? - Itzhak Venezia; Zur Shapira (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2004)
This paper compares the trading patterns of amateurs to that of professional investors during the days following the weekend. The comparison is based on all the daily transactions of a sample of both amateurs and professionally managed investors in a major brokerage house in Israel between 1994-1998. We find that weekends influence both amateurs and professional investors, however they affect professionals and amateurs in opposite directions. The results are consistent with previous hypotheses about the effects of the weekend on individuals and institutions in the US and with the way these differences may explain the weekend effect in returns in the US and in other markets. The results are also consistent with the absence of a weekend effect in returns in Israel during the period examined, since the conflicting effects of the weekend on individuals and professionally managed investors may have canceled each other.
Keywords: 330